Psicologia, metafísica e literatura: A descrição dos sentimentos profundos em Bergson - Rodrigues, Paulo César [UNESP] (FapUNIFESP (SciELO), 2013)
This paper aims to explore the relation between psychology, metaphysics and literature, through an examination of Bergon's Time and Free Will: An Essay on the Immediate Data of Consciousness, or, more precisely, through the description of deep feelings, which represent in the Essay a privileged moment for understanding the temporal structure of consciousness. However, this study will not be restricted only to Bergson's text and its descriptions of deep feelings (such as aesthetic and moral emotions), which would probably be repetitive. Instead, we shall use a work of literature (Guimarães Rosa's novel, Grande sertão: veredas) to exemplify the possibility of a qualitative description of stream of consciousness, revealing its temporal structure. We hope in this way to clarify the interaction between psychology, metaphysics and literature in the philosophy of Bergson.
Psychology, metaphysics and literature: The description of deep feelings in Bergson
Keywords: Deep feelings; Duration; Literature; Metaphysics; Psychology